Evaluación de la condición del pavimento flexible mediante método pci de la Av. Perimetral sur del cantón Pasaje. - Torres Montoya, Leither Elvis (My University, 2022)
The Perimetral Sur de Pasaje Avenue is frequented by vehicles heading towards the city of Cuenca or its surroundings, being an important artery that connects Machala with the highlands of the country. Because of this, there is an important exchange of products in both directions, which produces a lot of activity on the road, which is why it is pertinent to keep a record of the condition of the pavement in this important artery of the province. As the pavement is flexible, it requires regular maintenance to keep it in the best possible condition and thus avoid any inconvenience to users. In this report, the pavement condition index (PCI) is obtained for the South Perimeter Avenue of Pasaje. The PCI method diagnoses and quantifies (visual evaluation method) the different types of pavement deterioration according to their degree of severity, in accordance with the ASTM D6433-07 Standard. The current average PCI is 17.27, which according to the Standard indicates that the condition of the flexible pavement analyzed is, very poor. The failures identified are, alligator skin with 21.19%, depression with 72.63%, longitudinal cracks with 3.13%, patching with 0.85%, voids with 1.78% and finally swelling with 0.42%.
La Av. Perimetral Sur de Pasaje frecuentan vehículos que se dirigen hacia la ciudad de Cuenca o sus alrededores, siendo una importante arteria que conecta Machala con la Sierra del País. Debido a ello se produce un intercambio importante de productos en ambos sentidos, lo que produce mucha actividad en la vía, motivo por el cual es pertinente llevar un registro de la condición del pavimento en esta arteria tan importante de la provincia. Al ser de pavimento flexible esto requiere un mantenimiento regular para conservarse en las mejores condiciones posibles y con ello evitar cualquier tipo de inconveniente con los usuarios. En este informe se realiza la obtención del índice de condición del pavimento (PCI) en la Avenida Perimetral Sur de Pasaje. En el método del PCI se diagnostican y cuantifican (método de evaluación visual) los diversos tipos de deterioros del pavimento según su grado de severidad, de acuerdo con la Normativa ASTM D6433-07. El PCI actual promedio es de 17.27 lo que según la Norma indica que el estado del pavimento flexible analizado es ,muy malo,. Las fallas identificadas son, piel de cocodrilo con 21.19%, depresión con 72.63%, grietas longitudinales con 3.13%, parcheo con 0.85%, huecos con 1.78% y finalmente hinchamiento con 0.42%.
Keywords: PAVIMENTO; FLEXIBLE; INDICE; CONDICION